Antioxidative activity of Ginkgo, Echinacea, and Ginseng tinctures - Masteikova, Rūta; Muselik, Jan; Bernatoniene, Jurga; Bernatoniene, Rūta (Medicina (Kaunas, Lithuania), 2007)
The aim of this study was to determine the amount of phenol compounds in tinctures prepared from Ginkgo leaves, Echinacea plant, and Ginseng roots and to evaluate the antioxidative activity of these preparations. We studied the antioxidative activity using the standard 2,2-diphenyl-1-picrylhydrazyl (DPPH.) radical cation scavenging and tyrosine nitration inhibition tests. The obtained findings showed that the amount of phenol compounds in the studied tinctures differed and ranged between 114 to 340+/-29 gallic acid equivalents (GAE) mg/100 mL. We found that the amount of phenol compounds in Ginkgo tincture was statistically significantly greater than that in Echinacea or Ginseng tinctures. The effectiveness of Ginkgo tincture was by 52.7% (P<0.01) lower (from 1343+/-11 mumol catechin/100 mL solution to 637+/-64 catechin/100 mL solution), compared to Echinacea tincture. Ginseng tincture was the weakest scavenger of free radicals--only 8+/-1 micromol catechin/100 mL solution. The inhibition of tyrosine nitration was by 34% (P<0.01) greater in Echinacea tincture, compared to Ginkgo tincture (from 892+/-36 micromol catechin/100 mL solution to 588+/-17 micromol catechin/100 mL solution). Ginseng tincture was the weakest inhibitor of tyrosine nitration--only 20+/-8 micromol catechin/100 mL solution, which was by 44.6 times less, compared to Echinacea tincture. Tests on DPPH. radical cation scavenging and inhibition of nitration showed that the antioxidative activity of Echinacea tincture was statistically significantly greater compared to that of Ginkgo or Ginseng tinctures. This allows us to conclude that antioxidative activity is determined not only by phenol compounds, but also by a complex of other components of medicinal raw material.
Keywords: Phenols; Echinacea; rostlinné přípravky; Chromatography, High Pressure Liquid; Free Radical Scavengers; Ginkgo biloba; antioxidancia; ženšen; Plant Preparations; Panax; Data Interpretation, Statistical; indikátory a reagencie; fenoly; Antioxidants; vysokoúčinná kapalinová chromatografie; Indicators and Reagents; interpretace statistických dat; scavengery volných radikálů